Pendampingan Pembelajaran Kitab Risalatul Mahid Bagi Santriwati di Madrasah Diniyah NU Desa Sidorejo Kabupaten Pekalongan - Arditya Prayogi; Siti Chofifah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This community service article discusses the study of the Risalatul Mahid book in implementing religious education in Madrasah Diniyah NU, Sidorejo Village, Pekalongan Regency. The discussion focused on the method and its application in learning, as well as assessment techniques after the implementation of learning. This service activity aims to strengthen the understanding of students/students regarding reproductive health, with the background that there are still people, especially teenage women who do not have a good understanding of their reproductive health. The learning method is carried out by providing material accompanied by discussions both online and offline, especially targeting female students at Madrasah Diniyah NU, Sidorejo Village. From the results of the activity, it can be concluded that in learning the Risalatul Mahid book, it is delivered according to the discussion chapter that will be taught and in its implementation it is responded well which can be seen from the increased understanding of participants related to reproductive health aspects.